2012
DOI: 10.1002/pssa.201100616
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically induced charge transfer in platinum–silicon heterosystems

Abstract: Electrochemical cyclovoltammetry experiments were carried out on the platinum surface of a platinum–silicon thin‐film device in sulfuric acid. The internal electronic barrier of the device allows the separation of ground state and excited state charge transfer events released by the electrochemical surface reaction. The traces of the device current show similar features as the cyclovoltammogram and can be discussed in terms of small deviations from the equilibrium state of the thin platinum film. The device cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Figure 2a shows a typical CV curve measured on the NDE with a 10 nm thick Pt film in the absence of a bias voltage (V bias = 0 V). All the observed features of the CV curve correspond to those reported in the literature 39 . The cathodic current corresponding to the HER (J cell ) is clearly seen near the zero potential.…”
Section: Resultssupporting
confidence: 87%
“…Figure 2a shows a typical CV curve measured on the NDE with a 10 nm thick Pt film in the absence of a bias voltage (V bias = 0 V). All the observed features of the CV curve correspond to those reported in the literature 39 . The cathodic current corresponding to the HER (J cell ) is clearly seen near the zero potential.…”
Section: Resultssupporting
confidence: 87%
“…10 For low dose samples, these cleaning cycles reveal the voltammogram shown in Figure 4, which is similar to what is obtained on bulk platinum. 11 Most characteristically, we observe the peaks attributed to H uptake and desorption, as well as the Pt oxidation and reduction peaks. Recently, Bürstel et al reported that the voltammetric response of Pt thin films on Si was similar in shape to that of bulk Pt, both when making contact directly to the Pt film (front-contact) and when making contact to the Si substrate (back-contact).…”
Section: Resultsmentioning
confidence: 78%
“…Only recently has there been a study on the relationship between charge-transfer at the Pt/Si interface and the surface electrochemistry. 1 We present the results of an investigation into the electrochemistry of silicon with varying coverages of platinum. Rather than depositing different amounts of platinum onto silicon wafers, we instead produced continuous films, and used ionic bombardment to strip varying amounts of the metal from the surface, as shown in Figure 1.…”
mentioning
confidence: 99%
“…In particular, features attributed to underpotential hydrogen adsorption, sulfate adsorption, and platinum oxidation are all recognizable. 19 Figure 4a shows cyclic voltammograms for different bombardment doses. The general shape of the voltammogram is maintained up to a dose of 3000, with only a slight decrease in the overall current density.…”
Section: Resultsmentioning
confidence: 99%